The Evolution of myExperiment. - Roure, D; Goble, C; Aleksejevs, S; Bechhofer, S; Bhagat, J; Cruickshank, D; Fisher, P; Kollara, N; Michaelides, D; Missier, P; Newman, DR; Ramsden, M; et al. (IEEE, 2010)
The myExperiment social website for sharing scientific workflows, designed according to Web 2.0 principles, has grown to be the largest public repository of its kind. It is distinctive for its focus on sharing methods, its researcher-centric design and its facility to aggregate content into sharable 'research objects'. This evolution of myExperiment has occurred hand in hand with its users. myExperiment now supports Linked Data as a step toward our vision of the future research environment, which we categorise here as'3 rd generation e-Research. © 2010 IEEE.